Antioxidant, polygalacturonase, pectin methylesterase and polyphenol oxidase activities of fresh-cut wax apple (Syzygium samarangense) treated with organic acids - Nur Izzah K.; Awang Y.; Ding P.; Hafiza Y.; Satar M.G.M. (Asian Network for Scientific Information, 2024)
Indexed by SCOPUS